2015
DOI: 10.1590/1678-775720150374
|View full text |Cite
|
Sign up to set email alerts
|

Effect of collagen sponge and fibrin glue on bone repair

Abstract: The ability of hemostatic agents to promote bone repair has been investigated using in vitro and in vivo models but, up to now, the results are inconclusive. Objective In this context, the aim of this study was to compare the potential of bone repair of collagen sponge with fibrin glue in a rat calvarial defect model.Material and Methods Defects of 5 mm in diameter were created in rat calvariae and treated with either collagen sponge or fibrin glue; untreated defects were used as control. At 4 and 8 weeks, his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 30 publications
(32 reference statements)
2
21
0
Order By: Relevance
“…The healing of calvarial bone defects usually begins by the margins of the surgical wound, from the periosteum or the dura mater . This minimal presence of neoformed bone tissue confirms the permanent character of the defect and is in agreement with the results of previous research, in which the filling of critical bone defects with collagen sponge alone resulted in minimal bone formation and persistence of the bone defect . Histological analyses also confirmed the data obtained through micro‐CT quantitative analysis, which showed that 5 mM Sr 2+ SR was inefficient in stimulating the regeneration of the bone defects.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The healing of calvarial bone defects usually begins by the margins of the surgical wound, from the periosteum or the dura mater . This minimal presence of neoformed bone tissue confirms the permanent character of the defect and is in agreement with the results of previous research, in which the filling of critical bone defects with collagen sponge alone resulted in minimal bone formation and persistence of the bone defect . Histological analyses also confirmed the data obtained through micro‐CT quantitative analysis, which showed that 5 mM Sr 2+ SR was inefficient in stimulating the regeneration of the bone defects.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, this material is biodegradable and promotes cell migration due to the presence of (Arg‐Gly‐Asp) domains that bind to cell surface integrins . The collagen sponge adopted in this study, also used as a carrier by other research groups, exhibits expansion capacity in addition to allowing adequate soaking of the test solution. Consequently, the sponge adapts to the size of the defect, promotes the efficient tamponade of the lesion and favors the formation of a stable clot, being reabsorbed after four to six weeks .…”
Section: Discussionmentioning
confidence: 99%
“…Santos Tde et al . () have proved that the collagen sponge can promote bone repair through the repair of calvarial defect on mice. However, due to the low porosity of stent and collagen sponge, it is hardly to provide enough space to ensure homogenous cells and extracellular matrix distribution (Ng et al .…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Till now, the collagen fibres have been widely used in the manufacture of biodegradable scaffolds and haemostatic sponges (Miyoshi et al 2001). Santos Tde et al (2015) have proved that the collagen sponge can promote bone repair through the repair of calvarial defect on mice. However, due to the low porosity of stent and collagen sponge, it is hardly to provide enough space to ensure homogenous cells and extracellular matrix distribution (Ng et al 2004).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Site-directed mutagenesis showed that the conserved polar and aromatic residues in PPC domains might play key roles in the binding and swelling of collagen. Collagen fibers have been widely used to manufacture biodegradable scaffolds and hemostatic sponges; however, the low porosity of stents and collagen sponges has limited the distribution of the extracellular matrix and the growth of homogenous cells (40,41). The collagen-binding and swelling capacities of PPC can be used to modify collagen fibers and create novel stents or sponges with high porosity ratios and good physical properties, which might be useful for facilitating cell proliferation and promoting tissue repair.…”
mentioning
confidence: 99%